The effects of organization intangible resources on smes performance in Nigeria: the role of Islamic work ethics as a moderator - Kareem, Olanrewaju author (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis, 2018)
The focus of this study is to examine the performance of SMEs in relation to knowledge management, market orientation, organization culture, and entrepreneurial orientation with the moderating effect of Islamic work ethics. Therefore, based on the existing studies on the Nigerian SMEs which limit their scope to either one city within the state or a particular state, this study covers six states namely; Kano (North West), Bauchi (North East), FCT (North Central), Lagos (South West), Anambra (South East) Rivers (South South) from the six geo-political zones in Nigeria as structured by federalism system. Each of these states have the highest number of SMEs in their zones.